On application of methods of regressive analysis in problems of structural identification under conditions of incomplete information about of measurement - Архипова, С. А. (Proceedings of National Aviation University (archive), 1998)
Considered is the possibility of application of methods of regressive analysis in solution of identification problems under conditions of absence of information about the peculiarity of measurement errors. We prove that this methods are inefficient for obtaining good results